The Influence of Brand Involvement, Online Brand Experience, and Self-Brand Image Congruence on Positive Word of Mouth Through Online Consumer Brand Engagement With Brand Love as a Mediating Variable (An Empirical Study on Tokopedia Users in Padang City) - Nur Afifah; Yasri (PT. Hasba Edukasi Mandiri, 2025)
This study aims to prove and analyze the influence of brand involvement, online brand experience, and self-brand image congruence on word of mouth through customer engagement and brand love as mediating variables. This research was conducted on 230 customers in Padang City who shop through the Tokopedia marketplace. Selected respondents were Tokopedia customers who had shopped through the website at least twice in the last three months. The data collection process was carried out by distributing questionnaires directly. The data analysis method used was Structural Equation Modeling (SEM). The results of the hypothesis testing successfully found that stronger brand involvement and online brand experience will encourage online customer brand engagement on the Tokopedia marketplace, but self-brand image congruence does not have a significant effect on online customer brand engagement. In the direct effect testing stage, we also found that stronger self-brand image congruence in each customer will increase brand love. We also succeeded in proving that stronger brand love in customers will encourage the formation of positive word of mouth. In the indirect effect testing stage, it was found that customer brand engagement and online brand engagement were able to mediate the relationship between brand involvement and brand love on Tokopedia marketplace services, but online customer brand engagement did not mediate the relationship between self-brand image congruence and brand love on Tokopedia marketplace. In the next hypothesis testing stage, we successfully proved that when online customer brand engagement is higher, their brand love on Tokopedia services is higher. Then, in the final hypothesis, we found that brand love is able to mediate the relationship between online brand engagement and positive word of mouth about Tokopedia services.